Electrically enhanced, Nature-Driven microbial attenuation of chromate and dichloromethane in groundwater - Qingxia Li; Qinghao Zhang; Dandan Huang; Siming Chen; Baogang Zhang (Bioresource Technology, 2026)

Data-driven investigation of ship fuel consumption integrating causal inference and hierarchical analysis - Wenjie Cao; Xinjian Wang; Wei Zhang; Huanhuan Li; Siming Fang; Zaili Yang (Transportation Research Part D: Transport and Environment, 2026)

A physics-informed transformer framework for multi-step 6-DOF motion prediction of distressed vessels - Yingjie Yu; Xiufeng Zhang; Siming Zhang; Mingjie Li (Ocean Engineering, 2026)

Corrigendum to “Electrically enhanced, Nature-Driven microbial attenuation of chromate and dichloromethane in groundwater” [Bioresour. Technol. 459 (2026) 135175] - Qingxia Li; Qinghao Zhang; Dandan Huang; Siming Chen; Baogang Zhang (Bioresource Technology, 2026)

Engineering lignin-incorporated hydrogels for agricultural and environmental applications: From synthesis to sustainable implementation - Fuke Ai; Xiaolei Zhang; Bing Hu; Shin Ying Foong; Weidong Ye; Yameng Li; Quanguo Zhang; Pedram Fatehi; Siming You; Zhiping Zhang (Bioresource Technology, 2026)

Dynamic modeling of submarine cable laying using ALE-ANCF: Insights into cable tension and configuration - Wenyan Gu; Xiangqian Zhu; Xinyu Li; Yanliang Pei; Jinsheng Zhang; Siming Yang; Zhixun Yang (Ocean Engineering, 2026)

Stability of oil bodies under pulsed electric field exposure to rapeseed: New insights into improving oil extraction capacity - Qiqi Zhang; Jinling Hu; Yunyun Li; Bo Wang; Jing Wang; Jie Zhao; Siming Zhao; Caihua Jia; Jie Kuai; Guangsheng Zhou (Food Chemistry, 2026)

Mechanistic study on propoxate-induced neurotoxicity and addictive potential via blood-brain barrier disruption and GABAergic pathway activation - Renjuan Cao; Siming Ding; Jihong Cai; Jingxian Zhang; Xin Liu; Yuan Ren; Chao Liu (Toxicology, 2026)

Scalable fabrication of ultrathin LiIn@Cu composite anodes via roll-to-roll dip coating for high-energy-density batteries - Qihang Zhang; Anli Wang; Yifei Chen; Zihan Lin; Changyi Dong; Qiang Lu; Jixian Lv; Weike Yu; Siming Yang; Xiaoqun Qi; Jia Li; Fei Shen; et al. (Chemical Engineering Journal, 2026)

Synergistic control of Pseudomonas aeruginosa by LAB and phage for sustainable aquatic preservation - Siming Xue; Kairui Zhao; Rui Dong; Haichen Li; Ruizi Wang; Wei Cheng; Yuqi Fan; Qin Zhang; Ziyi Xue; Yujin Wu; Jun Zhang; Yanmei Sun; et al. (Food Bioscience, 2026)

Segmental tunnel with isolation layer in soil-rock transition under longitudinal excitation: experimental and numerical investigation - Siming Li; Yong Yuan; Roberto Cudmani; Jinghua Zhang; Mingqing Xiao; Haitao Yu (Transportation Geotechnics, 2026)

Seismic response of segmental tunnel in soil-rock strata under longitudinal excitation: experimental and numerical analysis - Siming Li; Yong Yuan; Haitao Yu; Jinghua Zhang; Mingqing Xiao; Roberto Cudmani (Soil Dynamics and Earthquake Engineering, 2026)

Microbial electrochemical reduction of chromate in groundwater driven by Thiobacillus denitrificans - Luyao Wang; Siming Chen; Song Wang; Xinxin Li; Baogang Zhang (Journal of Environmental Chemical Engineering, 2025)

Corrigendum to “Effects of herbaceous plant roots on tensile strength of root-soil composite in loess hilly region”. [Catena 260 (2025) 109423] - Sijing Zhang; Jianye Ma; Siming Liu; Longyu Zhang; Zhanbin Li; Fangtao She; Jiulong Ding; Peng Li; Chengcang Tian (CATENA, 2025)

Effects of herbaceous plant roots on tensile strength of root-soil composite in loess hilly region - Sijing Zhang; Jianye Ma; Siming Liu; Longyu Zhang; Zhanbin Li; Fangtao She; Jiulong Ding; Peng Li; Chengcang Tian (CATENA, 2025)

Selective kernel convolution with global attention mechanism for multitask change detection in optical and SAR images - Tonggen Yang; Liang Huang; Bo-Hui Tang; Zhitao Fu; Zhen Zhang; Zhongxi Ge; Man Zhang; Siming Pu (Earth Science Informatics, 2025)

A thermal-pore-chemical-mechanics model for large landslides in the unsaturated case - Huanhuan Zhang; Wei Liu; Siming He; Xiong Tang; Wei Hu (Bulletin of Engineering Geology and the Environment, 2025)

High-performance dynamic radiative regulation via controllable macroscopic materials modulation - Ya Huang; Xueke Wu; Siming Zhao; Baoshun Wang; Zhuojing Zhao; Di Gao; Run Li; Yunrui Li; Fei Wang; Fan Lan; Yanlong Zhao; Rufan Zhang (Science Bulletin, 2025)

Change detection in optical and SAR images by integrating fine-grained feature extraction and contextual transformation - Man Zhang; Liang Huang; Bohui Tang; Tonggen Yang; Siming Pu (Advances in Space Research, 2025)

Bioinspired ECM-specific microenvironment scaffold: A multi-biomimetic strategy spatially guides osteochondral regeneration - Kun Liu; Wuyan Xu; Lin Li; Wendong Zhang; Wei Wen; Shan Ding; Mingxian Liu; Changren Zhou; Siming Li; Qingqi Meng; Binghong Luo (Chemical Engineering Journal, 2025)

A galacturonan from sea buckthorn (Hippophae rhamnoides L.) berry modulates dyslipidemia by promoting hepatic lipolysis and mitochondrial oxidation - Yunpeng Sun; Weifeng Ni; Dongyi Wang; Jixiang Ren; Daqing Zhao; Shiting Yu; Shichao Liu; Shaojie Zhang; Siming Wang; Weinan Wang; Meichen Liu (Carbohydrate Polymers, 2025)

Novel metabolic pathways of bioelectrochemical vanadate reduction by Thiobacillus denitrificans without exogenous electron donor supplementation in groundwater - Luyao Wang; Siming Chen; Rui Li; Baogang Zhang (Water Research, 2025)

The role of lactate metabolism in retinoblastoma tumorigenesis and ferroptosis resistance - Zhihui Zhang; Junjie Tang; Yaoming Liu; Yinghao Wang; Jinmiao Li; Yang Gao; Chao Cheng; Shicai Su; Shuxia Chen; Siming Ai; Ping Zhang; Rong Lu (Tissue and Cell, 2025)

Decreasing the pH value would improve the swallowing characteristics of whey protein isolate-enriched thickened fluids for dysphagia populations - Zihang Cheng; Kedu Wang; Dongling Qiao; Bowen Li; Siming Zhao; Binjia Zhang (Food Research International, 2025)

Incorporating maltitol regulates the gel properties and structural features of κ-carrageenan-corn starch-soy protein isolate based quaternary system and its application of low glycemic index gummies - Xiaowen Pi; Lilin Zhu; Mengqian Xiang; Siming Zhao; Bowen Li; Dongling Qiao; Binjia Zhang (Food Chemistry, 2025)

Germination and fermentation synergistically tailor the starch structure within brown rice and the quality features of brown rice tea - Yabin Guo; Yang Xu; Siming Zhao; Dongling Qiao; Bowen Li; Binjia Zhang (Food Research International, 2025)

Encapsulated benzoic acid alleviated LPS-induced intestinal damage via NRF2 activation - Yanyan Zhang; Tianjiao Wang; Qing He; Mahmoud M. Abouelfetouh; Qin Fu; Siming Yao; Shiqiang Ju; Zhenlei Zhou; Qiao Li (Food Bioscience, 2025)

Genetic analysis and fine mapping reveal that AhRt3, which encodes an anthocyanin reductase, is responsible for red testa in cultivated peanuts - Yanyan Tang; Xiantao Zhou; Xin Li; Cai Zhou; Wenlin Wang; Mo Zhou; Zhicheng Hu; Xiaobei Li; Kaiyuan Zhang; Siming Wang; Zhihao Zhang; Hao Chen; et al. (Theoretical and Applied Genetics, 2025)

Review of Research Progress on the Impact of Submarine Groundwater Discharge on Pockmark Formation and Evolution - Zhengrong Zhang; Hongxian Shan; Xuezhi Feng; Zhentian Jia; Long Jiang; Siming Wang; Chaoqi Zhu (Journal of Marine Science and Engineering, 2025)
Pockmarks are globally distributed geomorphic features exhibiting diverse morphologies. Their geometric characteristics are commonly quantified by the radius-to-depth ratio. The evolutionary process of these features typically follows a cyclical pattern comprising initiation, expansion, stabilization, and decline. Submarine groundwater discharge (SGD), a seasonally modulated land–sea exchange process, exerts a significant influence on the formation and evolution of pockmarks. This influence is mediated through hydrodynamic forcing effects, sediment redistribution, and coupled chemical–biological interactions. This review systematically examines the formation mechanisms, evolutionary patterns, and primary controlling factors of pockmarks induced by SGD. It integrates recent research developments and global case studies to elucidate the dynamic interplay of multiple influencing factors. This study emphasizes the significance of interdisciplinary approaches in marine geological research and identifies key areas for future investigation. These insights aim to enhance risk assessment frameworks for marine hazards and inform marine spatial planning strategies.

Polysaccharide–dextrin thickened fluids for individuals with dysphagia: recent advances in flow behaviors and swallowing assessment methods - Kedu Wang; Zihang Cheng; Dongling Qiao; Fengwei Xie; Siming Zhao; Binjia Zhang (Critical Reviews in Food Science and Nutrition, 2025)

Correction: Cinnamaldehyde Alleviates Alveolar Epithelial Cell Injury in ALI by Inhibiting the CaMKII Pathway - Lei Liu; Hao Zhang; Siming Chen; Wankang Dian; Zhou Zheng (Cell Biochemistry and Biophysics, 2025)

Benzimidazole-containing polyimide-based sensors for sequential detection of fluoride ions and water content in organic solvents - Manyu Lian; Siming Liang; Leilei Yuan; Hao Ding; Guotao Huang; Liyong Tian; Ningbo Yi; Yangfan Zhang; Qinghua Wu; Longfei Fan; Feng Gan; Yancheng Wu (Journal of Environmental Chemical Engineering, 2025)

Prediction of near-surface conditions following the 2023/24 sudden stratospheric warming by the S2S project models - Jian Rao; Xiaoqi Zhang; Qian Lu; Siming Liu (Atmospheric Research, 2025)

Brazilin alleviates acute lung injury via inhibition of ferroptosis through the SIRT3/GPX4 pathway - Xiaopei Yan; Li Xu; Chang Qi; Yiling Chang; Juanjuan Zhang; Ning Li; Baoyu Shi; Bo Guan; Siming Hu; Chao Huang; Hui Wang; Ying Chen; et al. (Apoptosis, 2025)

Review of Research Progress on the Influence of Groundwater Discharge on Seabed Stability - Zhentian Jia; Hongxian Shan; Hanlu Liu; Zhengrong Zhang; Long Jiang; Siming Wang; Yonggang Jia; Yongzheng Quan (Journal of Marine Science and Engineering, 2025)
Submarine groundwater discharge (SGD) refers to the flow of groundwater that enters seawater through the seabed surface at the edge of the coastal shelf. During this discharge process, seepage and initiation can easily trigger seabed instability, which significantly influences the breeding, occurrence, and evolution of marine geological events. The narrow distribution of land near the coastline and the substantial flux of groundwater discharge are closely associated with typical seabed geological events, such as submarine landslides and collapse pits, which are prevalent in the sea area. This paper analyzes the current research status of SGD both domestically and internationally, elucidates the interaction mechanisms between groundwater discharge and the seabed, and integrates existing studies on discharge-induced slope instability, collapse pit formation, and seabed erosion and resuspension. It summarizes and evaluates the existing research on the influence of seabed groundwater discharge on the evolution of seabed geological structures, identifies key scientific problems that urgently need to be addressed, and proposes future research directions that require further emphasis. Additionally, the paper conducts research on the mechanisms by which groundwater discharge affects seabed stability, providing valuable insights for the study of coastal zones in China. It also offers a scientific basis for enhancing the understanding of the generation mechanisms of marine geological events and improving the technological capabilities for their prevention and control.

Integrative transcriptomic, proteomic and metabolomic analyses yields insights into muscle fiber type in cattle - Xiaofan Tan; Ruixue Zhao; Jing Chen; Zhiwei Yan; Xin Sui; Heling Li; Qiao Li; Xuehai Du; Yangzhi Liu; Siming Yao; Ying Yang; David M. Irwin; et al. (Food Chemistry, 2025)

Acetated starch inclusion to tailor the hierarchical structure and sol-gel features of middle gluten wheat starch-based binary matrices - Bowen Chen; Guojia Jin; Shengsong Ji; Dongling Qiao; Siming Zhao; Binjia Zhang (Food Hydrocolloids, 2025)

Insight of soy protein isolate to decrease the gel properties corn starch based binary system: Rheological and structural investigation - Xiaowen Pi; Lilin Zhu; Mengqian Xiang; Siming Zhao; Zihang Cheng; Dongling Qiao; Binjia Zhang (Food Hydrocolloids, 2025)

The impact of school activity space layout on children's physical activity levels during recess: An agent -based model computational approach - Jiameng Cui; Xue Meng; Siming Qi; Junwen Fan; Wenxuan Yu; Hongxing Liu; Xiang Wang; Yu Zhang (Building and Environment, 2025)

An investigation on traction for deep-sea mining vehicle considering the interference effect between adjacent grousers - Mingshuai Xi; Fei Sha; Yuhang Zuo; Jingze Xu; Siming Zhang; Zeqian Li (Ocean Engineering, 2025)

The development of thickened fermented rice milk formulation for people with dysphagia: A view of multiple in vitro simulation methods - Zexue Lin; Lingling Ma; Bowen Li; Siming Zhao; Binjia Zhang (Food Research International, 2025)

Resolving differences in digestion features of cooked rice and wheat noodles: A view from starch multiscale structure - Zihang Cheng; Siming Zhao; Dongling Qiao; Xiaowen Pi; Binjia Zhang (Food Chemistry, 2025)

Incorporating κ-carrageenan regulates the gel properties and structural characteristics of corn starch-soy protein isolate based ternary system - Zihang Cheng; Mengqian Xiang; Dongling Qiao; Siming Zhao; Xiaowen Pi; Binjia Zhang (Food Hydrocolloids, 2025)

Effect of bisphenol F on reproductive function in F1 generation male mice and its potential mechanisms - Bo Li; Siming Huo; Jiayu Du; Xuliang Zhang; Jian Zhang; Miao Song; Yanfei Li (Environmental Pollution, 2025)

Understanding the application-related features of sweet potato starch varying in multi-scale supramolecular structure - Yabin Guo; Dongling Qiao; Siming Zhao; Xiaowen Pi; Bowen Li; Kai Zhang; Binjia Zhang (Carbohydrate Polymers, 2025)

Enhanced chitinase production by Bacillus paralicheniformis GXMU-J23.1: Optimization, genomic insights, and chitin degradation mechanism - Junjie Xie; Ligang Zhang; Kexin Yang; Hongyan Zhang; Mingguo Jiang; Siming Liao; Dengfeng Yang; Naikun Shen (Bioresource Technology, 2025)

Characteristics of Dissolved Inorganic Carbon (DIC) in the Western Coast of the Taiwan Strait Using a Shipboard Measurement - Jiehua Hu; Jinpei Yan; Hang Yang; Siming Huang; Siying Dai; Xiaoke Zhang; Shanshan Wang; Shuhui Zhao (Journal of Marine Science and Engineering, 2024)
An online dissolved inorganic carbon (DIC) monitoring system was produced to achieve high spatial and temporal resolution in DIC data from the western Taiwan Strait (WTS) during the summer. Surface seawater DIC, salinity, dissolved organic carbon (DOC), Chl-a, and NO3− samples were collected, as well as the vertical profiles of DIC, to understand DIC variations in the WTS. The results showed that the range of DIC levels in the surface seawater from the WTS was from 1.68 to 2.21 mmol/L (Mmol), with an average of 1.93 ± 0.19 Mmol, which was consistent with the sampling results using titration determination, with an average of 1.98 ± 0.12 Mmol. A high correlation (R2 = 0.96) was presented between the online monitoring and sampling detection of DIC, indicating that DIC could be measured with high accuracy using the online monitoring system. The spatial distribution of DIC was similar to that of salinity, but it was different from that of DOC and Chl-a. The DIC concentration positively correlated with salinity (R2 = 0.51) and presented a negative correlation (R2 = 0.92) with seawater temperature. However, the surface seawater DIC was almost independent from DOC and Chl-a in the observation sea areas. The DIC levels first increased and then decreased with the depth, with the highest DIC concentration occurring in the subsurface water at about 10 m, which was similar to the profiles of salinity and Chl-a in the northern and southern areas of the WTS. The profiles of DIC, salinity, NO3−, and Chl-a were almost independent from the water depth in the central WST. This indicated that seawater DIC in the WTS was mainly affected by seawater temperature, salinity, and the vertical mixing of sea water, but it was less impacted by TOC and Chl-a.

Microplastics alter the migration and transformation of vanadium in the riverine sediment environment - Siming Chen; Xinyue Zhang; Luyao Wang; Cuibai Chen; Jiamin Huang; Baogang Zhang (Science of The Total Environment, 2024)

Effects of microplastics separate exposure and co-exposure to 17β-estradiol on the productive performance of juvenile female Chinese mitten crab (Eriocheir sinensis) - Yang Fu; Jian Zhang; Yilong Cui; Bo Li; Siming Huo; Jiayu Du; Yanfei Li (Science of The Total Environment, 2024)

Neurotoxic effects of perinatal exposure to Bisphenol F on offspring mice - Siming Huo; Bo Li; Jiayu Du; Xuliang Zhang; Miao Song; Yanfei Li (Environmental Pollution, 2024)

The toxic effects and mechanisms of maternal exposure to Bisphenol F during gestation and lactation on lungs in female offspring mice - Jiayu Du; Siming Huo; Bo Li; Xuliang Zhang; Jian Zhang; Yang Fu; Bing Shao; Yanfei Li; Miao Song (Environmental Pollution, 2024)

Regeneration of CO2 from CO2-rich absorbents using hollow fiber membrane contactors in liquid–liquid extraction mode - Siming Chen; Chunjin Zhang; Jingchao Liu (Chemical Engineering Journal, 2024)

A Thermo-Poro-Mechanics Model Predicts the Transition from Creep to Rapid Movement of Large Landslides - Huanhuan Zhang; Wei Liu; Siming He; Wei Hu (Rock Mechanics and Rock Engineering, 2024)

Cinnamaldehyde Alleviates Alveolar Epithelial Cell Injury in ALI by Inhibiting the CaMKII Pathway - Lei Liu; Hao Zhang; Siming Chen; Wankang Dian; Zhou Zheng (Cell Biochemistry and Biophysics, 2024)

Experimental study on human evacuation onboard passenger ships considering heeling angle and opposite directions - Siming Fang; Zhengjiang Liu; Xinjian Wang; Ben Matellini; Jin Wang; Zaili Yang; Xinyu Zhang; Bo Wan; Shengke Ni (Ocean Engineering, 2024)

Activation of the NLRP3-CASP-1 inflammasome is restrained by controlling autophagy during Glaesserella parasuis infection - Chaoxiong Yue; Jinquan Li; Siming Zhang; Ruyi Ma; Mingjiao Suo; Yiwen Chen; Hui Jin; Yan Zeng; Yushan Chen (Veterinary Microbiology, 2024)

Controlling sodium chloride concentration modulates the supramolecular structure and sol features of wheat starch-acetylated starch binary matrix - Shengsong Ji; Siming Zhao; Dongling Qiao; Yan Xu; Caihua Jia; Meng Niu; Binjia Zhang (Carbohydrate Polymers, 2024)

The pivotal role of secondary nutrients and micronutrients in regulating fruit quality and root exudates metabolism profile of citrus - Yanni Tang; Wei Lou; Xiang Yan; Shiqian Li; Pengwei Wang; Yingjie Zhou; Ting Zhan; Siming Zhang; Chengxiao Hu; Xu Wang; Hanliang Liu; Qiling Tan; et al. (Plant and Soil, 2024)

Do E-governance, mineral resources, and policy stringency facilitate economic growth in selected resource-rich countries - Wenjun Wu; Zhilong Zhao; Siming Yu; Minyuan Zhang (Resources Policy, 2024)

Unveiling the inverse antimicrobial impact of a hetero-chitooligosaccharide on Candida tropicalis growth and biofilm formation - Yangyang Liu; Ruilian Li; Yuchen Zhang; Siming Jiao; Tong Xu; Yuhang Zhou; Yujing Wang; Jinhua Wei; Wei Du; Morihisa Fujita; Yuguang Du; Zhuo A. Wang (Carbohydrate Polymers, 2024)

Mechanism of the solubility increase of rice protein-ovalbumin co-assembly and its great potential as an emulsifier in high internal phase emulsion - Zufu Song; Siming Zhao; Xiaoli Zhang; Qing Zhang; Yu Han; Meng Niu; Yan Xu (Journal of Cereal Science, 2024)

Ion presence during thermal processing modulates the performance of rice albumin/anthocyanin binary system - Yabin Guo; Ruolan Fang; Yiyuan Zhen; Dongling Qiao; Siming Zhao; Binjia Zhang (Food Research International, 2024)

Corrigendum to “Necroptosis and NLPR3 inflammasome activation mediated by ROS/JNK pathway participate in AlCl3-induced kidney damage” [Food Chem. Toxicol. 178 (2023) 113915] - Jiayu Du; Xuliang Zhang; Jian Zhang; Siming Huo; Bo Li; Qi Wang; Miao Song; Bing Shao; Yanfei Li (Food and Chemical Toxicology, 2024)

Anticancer effect of hUC-MSC-derived exosome-mediated delivery of PMO-miR-146b-5p in colorectal cancer - Siming Yu; Ran Liao; Lu Bai; Madi Guo; Yu Zhang; Yumin Zhang; Qi Yang; Yushuai Song; Zhiwei Li; Qingwei Meng; Shubin Wang; Xiaoyi Huang (Drug Delivery and Translational Research, 2024)
Antisense oligonucleotide (ASO) is a novel therapeutic platform for targeted cancer therapy. Previously, we have demonstrated that miR-146b-5p plays an important role in colorectal cancer progression. However, a safe and effective strategy for delivery of an ASO to its targeted RNA remains as a major hurdle in translational advances. Human umbilical cord mesenchymal cell (hUC-MSC)–derived exosomes were used as vehicles to deliver an anti-miR-146b-5p ASO (PMO-146b). PMO-146b was assembled onto the surface of exosomes (e) through covalent conjugation to an anchor peptide CP05 (P) that recognized an exosomal surface marker, CD63, forming a complex named ePPMO-146b. After ePPMO-146b treatment, cell proliferation, uptake ability, and migration assays were performed, and epithelial-mesenchymal transition progression was evaluated in vitro. A mouse xenograft model was used to determine the antitumor effect and distribution of ePPMO-146b in vivo. ePPMO-146b was taken up by SW620 cells and effectively inhibited cell proliferation and migration . The conjugate also exerted antitumor efficacy in a xenograft mouse model of colon cancer by systematic administration, where PPMO-146b was enriched in tumor tissue. Our study highlights the potential of hUC-MSC-derived exosomes anchored with PPMO-146b as a novel safe and effective approach for PMO backboned ASO delivery. Graphical Abstract Schematic illustration of the preparation of an exosomal anchor peptide (CP05)-PMO that conjugately binds to exosomes from hUC-MSCs (ePPMO-146b) and the antitumor effect of ePPMO-146b in CRC, which occurs through the inhibition of Smad signaling and epithelial–mesenchymal transition.

The hepatotoxicity of hexafluoropropylene oxide trimer acid caused by apoptosis via endoplasmic reticulum-mitochondrial crosstalk - Jiayu Du; Xuliang Zhang; Bo Li; Siming Huo; Jian Zhang; Yang Fu; Miao Song; Bing Shao; Yanfei Li (Science of The Total Environment, 2024)

Blocking-baffle mechanism of vegetation to rock avalanche on the forested slope of the east Sichuan-Tibet Mountains - Yong Wu; Zhang-qing Wang; Xin-po Li; Siming He; Xiao-qin Lei (Landslides, 2024)

Protective effect of retaining wall on rock avalanche: A case study of Nayong rock avalanche in China - Zhongfu Wang; Fengge Shi; Siming He; Xusheng Zhang; Jingying Wang; Enlong Liu (Journal of Mountain Science, 2024)

Incorporating edible oil during cooking tailors the microstructure and quality features of brown rice following heat moisture treatment - Yabin Guo; Ruolan Fang; Zhuoting Wu; Gaolei Xi; Dongling Qiao; Genfa Wang; Ting Cui; Liang Zhang; Siming Zhao; Binjia Zhang (Food Research International, 2024)

Biodegradable copper peroxide decorated hollow polydopamine nanocomposite as effective chloroperoxidase delivery carrier for enhancing enzyme dynamic therapy via self-activated cascade reactions - Weiwei Wu; Yan Yang; Yu Zhang; Yina Zeng; Zhuoying Liang; Xiling Song; Yadong Huang; Wei Xue; Siming Yu (Chemical Engineering Journal, 2024)

Effect of vegetation growth on morphological traits of vegetation and biomechanical features of roots - Yi Zhang; Wei Liu; Siming He (Plant and Soil, 2024)

Hexafluoropropylene oxide trimer acid exposure triggers necroptosis and inflammation through the Wnt/β-catenin/NF-κB axis in the liver - Xuliang Zhang; Bo Li; Siming Huo; Jiayu Du; Jian Zhang; Miao Song; Bing Shao; Yanfei Li (Science of The Total Environment, 2023)

Importance sampling-based probabilistic performance modeling of low-, mid- and high-strength pipelines under coupling effect of hydrogen-induced damage and corrosion - Yihuan Wang; Zhenwei Zhang; Siming Liu; Ailin Xia; Ruiling Li; Guojin Qin (Process Safety and Environmental Protection, 2023)

Enrichment of resistant starch in starch-protein hydrolysate binary matrix by modulating pH during thermal processing - Cuihong Dai; Zihang Cheng; Yanyu Chen; Dongling Qiao; Gaolei Xi; Qiuling Wang; Fan Zhu; Siming Zhao; Binjia Zhang (Food Research International, 2023)

A 26-week repeated dose toxicity evaluation of sporoderm-removed Ganoderma lucidum spores in rats - Lijuan Xia; Ruimin Sun; Liyan Zhang; Jinrong Li; Chengda Zhang; Qian Yang; Lili Zhang; Siming Zhang; Hanbo Wang; Hanying Lyu; Wanqiang Lyu; Zhenhao Li; et al. (Food and Chemical Toxicology, 2023)

Dibutyl phthalate induces liver fibrosis via p38MAPK/NF-κB/NLRP3-mediated pyroptosis - Siming Huo; Bo Li; Jiayu Du; Xuliang Zhang; Jian Zhang; Qi Wang; Miao Song; Yanfei Li (Science of The Total Environment, 2023)

Ingesting retrograded rice (Oryza sativa) starch relieves high-fat diet induced hyperlipidemia in mice by altering intestinal bacteria - Zihang Cheng; Nannan Li; Zhining Chen; Kaikai Li; Dongling Qiao; Siming Zhao; Binjia Zhang (Food Chemistry, 2023)

Genome-resolved metagenomic insight into vanadate and ammonium elimination in sulfur-based autotrophic biosystem - Wenyue Yan; Siming Chen; Min Li; Sitong Liu; Baogang Zhang (Chemical Engineering Journal, 2023)

3D-exosomes laden multifunctional hydrogel enhances diabetic wound healing via accelerated angiogenesis - Han Peng; Huichen Li; Xi Zhang; Jiezhang Tang; Yongping Liang; Lipeng Qiao; Yun Zhu; Mengmeng Hou; Siming Wei; Zhaoxiang Zhang; Chaohua Liu; Xinmao Li; et al. (Chemical Engineering Journal, 2023)

Electrical stimulation promotes synchronous nitrobenzene bio-degradation and vanadate bio-reduction - Siming Chen; Jin Li; Zongyan Li; Shuo Li; Baogang Zhang (Chemical Engineering Journal, 2023)

Creep-to-Runout Transition of Large Landslides Controlled by Frictional Velocity Strengthening and Weakening (Vajont 1963, Italy) - Huanhuan Zhang; Siming He; Wei Liu; Yu Deng; Wei Hu (Rock Mechanics and Rock Engineering, 2023)

Shaking table test on a segmental tunnel crossing soil-rock interface under transverse sinusoidal excitations - Siming Li; Yong Yuan; Haitao Yu; Jinghua Zhang; Roberto Cudmani (Tunnelling and Underground Space Technology, 2023)

Blockchain technology applications in waste management: Overview, challenges and opportunities - Peng Jiang; Lei Zhang; Siming You; Yee Van Fan; Raymond R. Tan; Jiří Jaromír Klemeš; Fengqi You (Journal of Cleaner Production, 2023)

The impact of GmTSA and GmALS on soybean salt tolerance: uncovering the molecular landscape of amino acid and secondary metabolism pathways - Minghao Sun; Siming Wei; Jiarui Liu; Luyao Wang; Yu Zhang; Limin Hu; Jingxi Piao; Zhao Liang; Hongwei Jiang; Dawei Xin; Ying Zhao; Qingshan Chen; et al. (Theoretical and Applied Genetics, 2023)

Kif15 deficiency contributes to depression-like behavior in mice - Junpei Wang; Qifeng Tu; Siming Zhang; Xiaomei He; Chao Ma; Xiaowei Qian; Ronghua Wu; Xinyu Shi; Zhangyi Yang; Yan Liu; Zhangji Dong; Mei Liu (Metabolic Brain Disease, 2023)

Dibutyl phthalate causes heart damage by disrupting Ca2+ transfer from endoplasmic reticulum to mitochondria and triggering subsequent pyroptosis - Bo Li; Siming Huo; Jiayu Du; Xuliang Zhang; Jian Zhang; Qi Wang; Miao Song; Yanfei Li (Science of The Total Environment, 2023)

Degradation characteristics of intracellular and extracellular ARGs during aerobic composting of swine manure under enrofloxacin stress - Jiaojiao Xu; Jielan Huang; Longhai Chen; Majian Chen; Xin Wen; Pengfei Zhang; Siming Li; Baohua Ma; Yongde Zou; Yan Wang; Xindi Liao; Yinbao Wu (Chemical Engineering Journal, 2023)

Necroptosis and NLPR3 inflammasome activation mediated by ROS/JNK pathway participate in AlCl3-induced kidney damage - Jiayu Du; Xuliang Zhang; Jian Zhang; Siming Huo; Bo Li; Qi Wang; Miao Song; Bing Shao; Yanfei Li (Food and Chemical Toxicology, 2023)

Isoalantolactone relieves depression-like behaviors in mice after chronic social defeat stress via the gut-brain axis - Siming Wang; Qihan Cai; Lu Xu; Yanan Sun; Mengmeng Wang; Yu Wang; Lili Zhang; Keqing Li; Zhiyu Ni (Psychopharmacology, 2023)
Rationale The management of depression continues to be challenging despite the variety of available antidepressants. Herbal medicines are used in many cultures but lack stringent testing to understand their efficacy and mechanism of action. Isoalantolactone (LAT) from Elecampane ( Inula helenium ) improved the chronic social defeat stress (CSDS)-induced anhedonia-like phenotype in mice comparable to fluoxetine, a selective serotonin reuptake inhibitor (SSRI). Objectives Compare the effects of LAT and fluoxetine on depression-like behaviors in mice exposed to CSDS. Result The CSDS-induced decrease in protein expression of postsynaptic density (PSD95), brain derived neurotrophic factor (BDNF), and glutamate receptor subunit-1 (GluA1) in the prefrontal cortex was restored by LAT. LAT showed robust anti-inflammatory activity and can lessen the increase in IL-6 and TNF-α caused by CSDS. CSDS altered the gut microbiota at the taxonomic level, resulting in significant changes in α- and β-diversity. LAT treatment reestablished the bacterial abundance and diversity and increased the production of butyric acid in the gut that was inhibited by CSDS. The levels of butyric acid were negatively correlated with the abundance of Bacteroidetes , and positively correlated with those of Proteobacteria and Firmicutes across all treatment groups. Conclusions The current data suggest that, similar to fluoxetine, LAT show antidepressant-like effects in mice exposed to CSDS through the modulation of the gut-brain axis.

Towards designing dysphagia foods: Recent advances in influencing factors and computer modeling for the swallowing of thickened fluids - Shuhan Liu; Dongling Qiao; Zihang Cheng; Fengwei Xie; Siming Zhao; Binjia Zhang (Trends in Food Science & Technology, 2023)

Power performance of an asymmetric wave energy converter near a partial reflection wall - Binzhen Zhou; Qi Zhang; Jianjian Hu; Peng Jin; Hengming Zhang; Siming Zheng (Ocean Engineering, 2023)

Incorporating acetylated starch regulates the structure and sol-gel performance of wheat starch-based binary system - Shengsong Ji; Dongling Qiao; Siming Zhao; Yan Xu; Caihua Jia; Meng Niu; Binjia Zhang (Food Hydrocolloids, 2023)

Bioleaching performance of vanadium-bearing smelting ash by Acidithiobacillus ferrooxidans for vanadium recovery - Xiaoxiao Guo; Siming Chen; Yawei Han; Chunbo Hao; Xiujuan Feng; Baogang Zhang (Journal of Environmental Management, 2023)

Mitophagy alleviates AIF-mediated spleen apoptosis induced by AlCl3 through Parkin stabilization in mice - Miao Song; Jian Zhang; Siming Huo; Xuliang Zhang; Yilong Cui; Yanfei Li (Food and Chemical Toxicology, 2023)

Physicochemical and functional properties of chitosan-based edible film incorporated with Sargassum pallidum polysaccharide nanoparticles - Ke Zhang; Qing Chen; Jie Xiao; Lijun You; Siming Zhu; Chao Li; Xiong Fu (Food Hydrocolloids, 2023)

Understanding spatial-temporal travel demand of private and shared e-bikes as a feeder mode of metro stations - Siming Liu; Fan Zhang; Yanjie Ji; Xinwei Ma; Yong Liu; Shuo Li; Xizhen Zhou (Journal of Cleaner Production, 2023)

Hexafluoropropylene oxide trimer acid causes fibrosis in mice liver via mitochondrial ROS/cGAS-STING/NLRP3-mediated pyroptosis - Xuliang Zhang; Jiayu Du; Siming Huo; Bo Li; Jian Zhang; Miao Song; Bing Shao; Yanfei Li (Food and Chemical Toxicology, 2023)

Role of the in-situ-produced dextran by lactic acid bacteria in the texture modification of pea flour pastes - Jike Shuai; Lingyan Zhang; Zhimin Hu; Caihua Jia; Meng Niu; Siming Zhao; Yan Xu (Food Research International, 2023)

On the supraglacial rock avalanches: Thermo-hydro-mechanical analysis considering ice-water phase transition - Chuan He; Enlong Liu; Siming He; Jianhai Zhang; Haotian Wei (Geomorphology, 2023)

Review of explainable machine learning for anaerobic digestion - Rohit Gupta; Le Zhang; Jiayi Hou; Zhikai Zhang; Hongtao Liu; Siming You; Yong Sik Ok; Wangliang Li (Bioresource Technology, 2023)

Review of biochar production via crop residue pyrolysis: Development and perspectives - Yize Li; Rohit Gupta; Qiaozhi Zhang; Siming You (Bioresource Technology, 2023)

Experimental investigation on the hydrodynamic effects of heave plates used in floating offshore wind turbines - Lixian Zhang; Wei Shi; Yuxin Zeng; Constantine Michailides; Siming Zheng; Ying Li (Ocean Engineering, 2023)

Reconstruction of dynamics processes of Tagharma rock avalanche in Pamir Plateau: Geomorphology and sedimentology implications - Lei Zhu; Siming He; Xiaoqin Lei; Zongji Yang; Jihao Jian; Yi Zhang; Yong Wu; Jiang Li (Engineering Geology, 2023)

T-2 toxin inhibits osteoblastic differentiation and mineralization involving mutual regulation between Wnt signaling pathway and autophagy - Jian Zhang; Peiyan Wang; Miao Song; Xuliang Zhang; Siming Huo; Jiayu Du; Bo Li; Zheng Cao; Yanfei Li (Chemico-Biological Interactions, 2023)

Refined-JinQi-JiangTang tablet ameliorates hypertension through activation of FGF21/FGFR1 axis in fructose-fed rats - Siming Li; Xiaoling Li; Jing Fan; Xinhang Jia; Hemeng Wang; Fangxin Dong; Haoyang Mao; Chen Zhang; Wenfei Wang; Ye Jiang; Lijun Yan; Na Zhang (Journal of Natural Medicines, 2022)

Energy, economic, and environmental impacts of sustainable biochar systems in rural China - Siming You; Wangliang Li; Weihua Zhang; Hankwon Lim; Harn Wei Kua; Young-Kwon Park; Avanthi Deshani Igalavithana; Yong Sik Ok (Critical Reviews in Environmental Science and Technology, 2022)

Cavin-1 promotes M2 macrophages/microglia polarization via SOCS3 - Wei Huang; Yiyi Hong; Wenjing He; Li Jiang; Wen Deng; Biyan Peng; Fen Tang; Chaolan Shen; Qianqian Lan; Hui Huang; Haibin Zhong; Jian Lv; et al. (Inflammation Research, 2022)

Analysis of thermal impact of highway construction in plateau region on frozen soil corridor - Xinpo Sun; Jingyan Song; Yi Guo; Yingqian Zhang; Siming He (Arabian Journal of Geosciences, 2021)

Correction to: Stress and load-bearing structure analysis of the surrounding rock in a soft broken roadway - Guangming Zhao; Chongyan Liu; Siming Kao; Xiaobo Zhang; Xiang Cheng (Arabian Journal of Geosciences, 2020)

Fasudil attenuates glial cell-mediated neuroinflammation via ERK1/2 and AKT signaling pathways after optic nerve crush - Wei Huang; Qianqian Lan; Li Jiang; Wenya Yan; Fen Tang; Chaolan Shen; Hui Huang; Haibin Zhong; Jian Lv; Siming Zeng; Min Li; Zhongxiang Mo; et al. (Molecular Biology Reports, 2020)

Stress and load-bearing structure analysis of the surrounding rock in a soft broken roadway - Guangming Zhao; Chongyan Liu; Siming Kao; Xiaobo Zhang; Xiang Cheng (Arabian Journal of Geosciences, 2020)

Single-cell transcriptome analysis of the novel coronavirus (SARS-CoV-2) associated gene ACE2 expression in normal and non-obstructive azoospermia (NOA) human male testes - Xixi Liu; Yidong Chen; Wenhao Tang; Li Zhang; Wei Chen; Zhiqiang Yan; Peng Yuan; Ming Yang; Siming Kong; Liying Yan; Jie Qiao (Science China Life Sciences, 2020)

Simulating the process of the Jinshajiang landslide-caused disaster chain in October 2018 - Wei Liu; Nengpan Ju; Zhen Zhang; Zheng Chen; Siming He (Bulletin of Engineering Geology and the Environment, 2020)

Photocatalytic removal of elemental mercury via Ce-doped TiO2 catalyst coupling with a novel optical fiber monolith reactor - Feng Xin; Siming Ma; Jianping Yang; Yongchun Zhao; Junying Zhang; Chuguang Zheng (Environmental Science and Pollution Research, 2020)

Failure mechanism and dynamic processes of rock avalanche occurrence in Chengkun railway, China, on August 14, 2019 - Lei Zhu; Heng Liang; Siming He; Wei Liu; Qingyun Zhang; Gang Li (Landslides, 2020)

The expression and role of PIDD in retina after optic nerve crush - Fen Tang; Fan Xu; Ling Cui; Wei Huang; Li Jiang; Lifei Chen; Wenya Yan; Wenjing He; Chaolan Shen; Hui Huang; Jian Lv; Xin Zhao; et al. (Journal of Molecular Histology, 2020)

Characterization of a bifunctional alginate lyase as a new member of the polysaccharide lyase family 17 from a marine strain BP-2 - Guiyuan Huang; Shunhua Wen; Siming Liao; Qiaozhen Wang; Shihan Pan; Rongcan Zhang; Fu Lei; Wei Liao; Jie Feng; Shushi Huang (Biotechnology Letters, 2019)

Source characteristics and dynamics of the October 2018 Baige landslide revealed by broadband seismograms - Zhen Zhang; Siming He; Wei Liu; Heng Liang; Shuaixing Yan; Yu Deng; Xiuqiang Bai; Zheng Chen (Landslides, 2019)

Identification of novel miRNAs and their target genes in Eucalyptus grandis - Zheng Lin; Qingfen Li; Qi Yin; Jinyan Wang; Baolong Zhang; Siming Gan; Ai-Min Wu (Tree Genetics & Genomes, 2018)

Emission controls of mercury and other trace elements during coal combustion in China: a review - Yongchun Zhao; Jianping Yang; Siming Ma; Shibo Zhang; Huan Liu; Bengen Gong; Junying Zhang; Chuguang Zheng (International Geology Review, 2018)

A novel set of 223 EST-SSR markers in Casuarina L. ex Adans.: polymorphisms, cross-species transferability, and utility for commercial clone genotyping - Xiuyu Xu; Changpin Zhou; Yong Zhang; Weiqiang Zhang; Xianhua Gan; Huaxin Zhang; Yong Guo; Siming Gan (Tree Genetics & Genomes, 2018)

Molecular cloning, recombinant expression, and antifungal functional characterization of the lipid transfer protein from Panax ginseng - Kexin Cai; Jiawen Wang; Min Wang; Hui Zhang; Siming Wang; Yu Zhao (Biotechnology Letters, 2016)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

CspE is Overproduced by Temperature Downshift in the Acinetobacter johnsonii DBP-3 - Dan Su; Linlin Hao; Fuwang Chen; Siming Li; Ahmed Mohamed Abdelrahman; Yu Zhang; Hao Yu; Songcai Liu; Mingtang Li (Current Microbiology, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

Fibroblast growth factor (FGF21) protects mouse liver against d-galactose-induced oxidative stress and apoptosis via activating Nrf2 and PI3K/Akt pathways - Yinhang Yu; Fuliang Bai; Yaonan Liu; Yongbi Yang; Qingyan Yuan; Dehua Zou; Susu Qu; Guiyou Tian; Liying Song; Tong Zhang; Siming Li; YunYe Liu; et al. (Molecular and Cellular Biochemistry, 2015)

Characterization of fly ash from a circulating fluidized bed incinerator of municipal solid waste - Lin Zhang; Xiaowen Su; Zhixuan Zhang; Siming Liu; Yuxin Xiao; Mingming Sun; Jixin Su (Environmental Science and Pollution Research, 2014)

Seismic Stability Analysis of Pre-stressed Rope of Anti-slide Retaining Wall - Xiaoxi Zhang; Siming He; Qian Su; Wei Jiang (Geotechnical and Geological Engineering, 2013)

Comparative analysis of differentially expressed genes in Sika deer antler at different stages - Yu Zhao; Baojin Yao; Mei Zhang; Siming Wang; Hui Zhang; Wei Xiao (Molecular Biology Reports, 2013)

Antibody-Mediated Inhibition of Integrin α5β1 Blocks Neurotoxic Prion Peptide PrP106–126-Induced Activation of BV2 Microglia - Jiaxin Chang; Lifeng Yang; Mohammed Kouadir; Yun Peng; Siming Zhang; Fushan Shi; Xiangmei Zhou; Xiaomin Yin; Deming Zhao (Journal of Molecular Neuroscience, 2012)

Erratum to: Xeno-repopulation of Fah−/−Nod/Scid mice livers by human hepatocytes - BaoLiang Su; ChangCheng Liu; Dao Xiang; HaiBin Zhang; SiMing Yuan; MinJun Wang; Fei Chen; HaiYing Zhu; ZhiYing He; Xin Wang; YiPing Hu (Science China Life Sciences, 2011)

Xeno-repopulation of Fah−/−Nod/Scid mice livers by human hepatocytes - BaoLiang Su; ChangCheng Liu; Dao Xiang; HaiBin Zhang; SiMing Yuan; MinJun Wang; Fei Chen; HaiYing Zhu; ZhiYing He; Xin Wang; YiPing Hu (Science China Life Sciences, 2011)

The Role of β20–β21 Loop Structure in Insecticidal Activity of Cry1Ac Toxin from Bacillus thuringiensis - Yuan Lv; Ying Tang; Yunlei Zhang; Liqiu Xia; Faxiang Wang; Xuezhi Ding; Siming Yi; Wenping Li; Jia Yin (Current Microbiology, 2011)